Clinical phenotype and detailed investigation of children with undefined immunodeficiency. (29th September 2015) - Pemberton, L; Fox, H; Ramakrishnan, KA; Goswami, R; Efrem, E; Erlewyn-Lajeunesse, M; Williams, A; Faust, S
Abstract : Background and Aims: Immunodeficiency may cause infection, autoimmune disease and malignancy. There are over 100 defined primary immunodeficiency diseases (PIDs) with identified molecular defects. However, many children have recurrent or invasive infections where no specific PID diagnosis can be made. The natural history of children presenting with recurrent infections that resolve with age ("maturational immunodeficiency") is not well understood. The authors aimed to describe the clinical phenotype and natural history of children with undefined PID, and to identify those who may benefit from new additional screening approaches. Method: The clinical records of 351 children seen in a tertiary paediatric immunology and infection clinic between February 2006 and March 2009 were examined. Children with defined and undefined PID were identified (n=179) and specific clinical and laboratory data entered onto a database. Selected children underwent further innate function testing. Results: 36/179 (20%) had a defined PID. 143 had recurrent, persistent or invasive infection without a defined PID. The majority of the clinical parameters of these children, including the age of onset of infections and the system most frequently involved, did not differ significantly from those with defined PID. Children in the undefined PID group showed general lymphopenia which appears to normalise by the age of 10 years. In particular, CD3 CD4 T lymphocytes are relatively low during the first year of life but normalise thereafter. Total IgG was found to be decreased between 2–5 years, corresponding with the age group during which most clinical infections were experienced. 10/179 children in seven families appear to have abnormalities in new innate screening tests and are undergoing further detailed investigations (REC 09/H0502/4). Conclusion: Although some children with PID present early in infancy, children presenting with recurrent infection where no molecular defect is found often have clinical similarities to those with a defined PID diagnosis. While many of the 143 children may have a "maturational immunodeficiency" that resolves with age, the identification of those with novel defects may allow better therapeutic and prognostic interventions in the children likely to retain their unidentified immunodeficiency into adulthood.